Microstructure of the labial palps in the genera Aphrissa and Rhabdodryas (Lepidoptera: Pieridae, Coliadinae) from Mexico - Vargas-Fernández, Isabel; Llorente-Bousquets, Jorge Enrique (Revista de Biología Tropical, 2024)
Introduction: We studied the labial palps in three species belonging to two pierids from the Neotropical region. Our examination was based on ten male and eight female specimens from Mexican fauna. Objective: We describe the microstructure of the palp focusing on the Reuter's sensitive patch and the Palp-pit organ. Additionally, we aim to characterize the type, dimensions, and distribution of the sensilla. We aim to discern any variations between sexes and species. Methods: The labial palps were separated from the head and their scales were removed. Subsequently, the palps were mounted for observation under the scanning electron microscope. Micrographs were captured of both the bare and scaled palps. We measure the three segments and sensilla using Photoshop CS3 tools. Results: In both genera, the basal and mesial segments exhibit lateral flattening, whereas the distal segment is spherical or cylindrical. Significant differences were observed in the dimensions of the distal segment among the females of the two Aphrissa species compared to their male counterparts. The sensilla on the outer surface of the segments are chaetic and, while those at the base of the Palp-pit are coeloconic. The sensitive patch has numerous smooth, cone-like microtrichia, located on the basal segment and with lower density on the upper section of the Palp-pit, reaching the apex of the distal segment. Conclusion: The morphology displayed by the coeloconic and chaetic sensilla of the labial palps in Aphrissa and Rhabdodryas is consistent with that described for the coliadine butterfly Prestonia, as well as other previously studied genera. This suggests that the labial palps could serve as a system of microstructural characters in taxonomy.